Nuclear Respiratory Factor 1 (NRF-1) Controls the Activity Dependent Transcription of the GABA-A Receptor Beta 1 Subunit Gene in Neurons - Li, Zhuting; Cogswell, Meaghan; Hixson, Kathryn; Brooks-Kayal, Amy R.; Russek, Shelley J. (Frontiers in Molecular Neuroscience, 2018)
While the exact role of Beta 1 subunit-containing GABA-A receptors (GABARs) in brain function is not well understood, altered expression of the Beta 1 subunit gene (GABRB1) is associated with neurological and neuropsychiatric disorders. In particular, down-regulation of Beta 1 subunit levels is observed in brains of patients with epilepsy, autism, bipolar disorder, and schizophrenia. A pathophysiological feature of these disease states is imbalance in energy metabolism and mitochondrial dysfunction. The transcription factor, nuclear respiratory factor 1 (NRF-1), has been shown to be a key mediator of genes involved in oxidative phosphorylation and mitochondrial biogenesis. Using a variety of molecular approaches (including mobility shift, promoter/reporter assays, and overexpression of dominant negative NRF-1), we now report that NRF-1 regulates transcription of GABRB1 and that its core promoter contains a conserved canonical NRF-1 element responsible for sequence specific binding and transcriptional activation. Our identification of GABRB1 as a new target for NRF-1 in neurons suggests that genes coding for inhibitory neurotransmission may be coupled to cellular metabolism. This is especially meaningful as binding of NRF-1 to its element is sensitive to the kind of epigenetic changes that occur in multiple disorders associated with altered brain inhibition.